Adolescent alcohol use disrupts functional neurodevelopment in sensation seeking girls. (19th May 2020) - Zhao, Qingyu; Sullivan, Edith V.; Műller‐Oehring, Eva M.; Honnorat, Nicolas; Adeli, Ehsan; Podhajsky, Simon; Baker, Fiona C.; Colrain, Ian M.; Prouty, Devin; Tapert, Susan F.; Brown, Sandra A.; Meloy, Mary J.; et al.
Abstract: Exogenous causes, such as alcohol use, and endogenous factors, such as temperament and sex, can modulate developmental trajectories of adolescent neurofunctional maturation. We examined how these factors affect sexual dimorphism in brain functional networks in youth drinking below diagnostic threshold for alcohol use disorder (AUD). Based on the 3‐year, annually acquired, longitudinal resting‐state functional magnetic resonance imaging (MRI) data of 526 adolescents (12–21 years at baseline) from the National Consortium on Alcohol and Neurodevelopment in Adolescence (NCANDA) cohort, developmental trajectories of 23 intrinsic functional networks (IFNs) were analyzed for (1) sexual dimorphism in 259 participants who were no‐to‐low drinkers throughout this period; (2) sex‐alcohol interactions in two age‐ and sex‐matched NCANDA subgroups ( N = 76 each), half no‐to‐low, and half moderate‐to‐heavy drinkers; and (3) moderating effects of gender‐specific alcohol dose effects and a multifactorial impulsivity measure on IFN connectivity in all NCANDA participants. Results showed that sex differences in no‐to‐low drinkers diminished with age in the inferior‐occipital network, yet girls had weaker within‐network connectivity than boys in six other networks. Effects of adolescent alcohol use were more pronounced in girls than boys in three IFNs. In particular, girls showed greater within‐network connectivity in two motor networks with more alcohol consumption, and these effects were mediated by sensation‐seeking only in girls. Our results implied that drinking might attenuate the naturally diminishing sexual differences by disrupting the maturation of network efficiency more severely in girls. The sex‐alcohol‐dose effect might explain why women are at higher risk of alcohol‐related health and psychosocial consequences than men. Abstract : The diminishing sexual dimorphism in normal functional development during adolescence can be attenuated with drinking as girls exhibited greater disruption than boys in the maturation of network efficiency with more alcohol consumption. The sex–alcohol‐dose effect mediated by sensation seeking might explain why women are at heightened risk of greater alcohol‐related health and psychosocial consequences of hazardous drinking than men.